An exact optimization approach for personnel scheduling problems in the call center industry - Martins, Rita (2023)
Nowadays, the importance of the call center industry is increasing because they are a major means of communication between organizations and their customers. So, ensuring optimized personnel schedules in call centers has several advantages, such as reduced total labor costs, overstaffing, increased employee satisfaction, and acceptable waiting times. In this paper, we address the personnel scheduling problem in a 24/7 call center where the scheduling process is done manually. So, the main goal is to explore exact solution approaches to achieve better solutions while reducing the processing time. The proposed optimization model is an Integer Programming model to assign shifts to workers while minimizing the total penalization associated with employees’ time preferences. The model is tested with several instances, including randomly generated and real-world data instances. The quality of the model is assessed through a computational study of its linear relaxation, concluding that the model presents null integrality gaps in all the tested instances. Additionally, to evaluate the performance of the model when running large instances, several randomly generated instances were tested, achieving good computational results.